Across the ages - Meyer, Gabrielle (Minneapolis, Minnesota : Bethany House Publishers, a division of Baker Publishing Group, 2024)
"Caroline lives in two eras simultaneously-disguised as a pirate in 1727 and hunting down mobsters during Prohibition. The secret to her time-crossing gift lies with her mother, who disappeared in the Caribbean. While searching for her, Caroline finds more questions than answers as she embarks on a perilous journey through time"--
Keywords: Pirates -- Fiction; Mothers and daughters -- Fiction; Missing persons -- Investigation -- Fiction; Religious fiction; Christian fiction; Novels